Analysis of Adverse Drug Reaction of Favipiravir in COVID-19 Patients in Dr. Mohammad Hoesin General Hospital Palembang - Delita, Sari; Mira Yunita; Lucia Shinta Ratnaningtyas; Anggi Setyarini; Avega Wahyuningrum (Jurnal RSMH Palembang, 2023)
The coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2). Due to its heterogeneous disease severity and rapid transmission, the use of antiviral and immunomodulator drugs is crucial. Favipiravir, an antivirus, can treat SARS-CoV-2 due to its action on RNA Genome ACE2 receptor, therefore halting the viral replication. However, Adverse Drug Reactions (ADRs) monitoring of Favipiravir is recommended. The study design is a descriptive cross-sectional approach with prospective sampling. The study was held in May-July 2021 and aimed to determine the adverse effects of Favipiravir in confirmed COVID-19 patients in Dr. Mohammad Hoesin General Hospital Palembang. Adverse events such as gastrointestinal symptoms (nausea, vomiting, and decreased appetite) occurred in 2 of 170 patients (1.18%). Several side effects, such as an elevated liver enzyme, leukopenia, neutropenia, hyperuricemia, and increased triglyceride levels, cannot be assessed due to a lack of laboratory results before and after Favipiravir administration. Other side effects such as skin rash, asthma, rhinitis, nasopharyngeal pain, and oropharyngeal pain, were not found in the study.